Agricultural innovation in Latin America: understanding the private sector's role - Pomareda, Carlos; Hartwich, Frank (International Food Policy Research Institute, 2006)
For many years, governments and donors have promoted the generation of knowledge and technological innovations that improve farming and plant genetic resources in developing countries. Because of the “public good” nature of agricultural research for developing countries, it was assumed that the private sector would not invest sufficiently in producing knowledge and technologies that contribute to rural development and poverty alleviation there. So public agencies and aid organizations have initiated and subsidized agricultural research and innovation to supplement the knowledge and technology produced by private entities. Yet many of these publicly generated improvements have not been useful to farmers, processors, and agribusiness and hence have not been adopted on a wide scale. Others have not been transferred to those who would have contentedly absorbed them. At the same time, the production and marketing technologies for the fastest-growing products, such as fresh fruits and vegetables, have been introduced mostly by the private sector. In this context, it is crucial to revisit the role the private sector can play in generating knowledge and technology for agricultural development. What functions do farm input providers, farmers, processors, traders, and exporters have in agricultural innovation processes, and how can they become more directly involved in the financing, generation, diffusion, and adoption of new knowledge and technologies?